Legible Sovereignties : Rhetoric, Representations, and Native American Museums - King, Lisa (Lisa Michelle) (Book collections on Project MUSE., 2017)
"An interdisciplinary work that draws on the fields of rhetorical studies, Native American and Indigenous studies, and museum studies, Legible Sovereignties considers the creation, critical reception, and adaptation of Indigenous self-representation in three diverse Indigenously oriented or owned institutions. King tracks the exhibit spaces at the Saginaw Chippewa Indian Tribe of Michigan's Ziibiwing Center, Haskell Indian Nation University's Cultural Center and Museum, and the Smithsonian's Washington, DC branch of the National Museum of the American Indian over their first ten years, from their opening until the summer of 2014. Far from formulaic, each site has developed its own rhetorical approaches to reaching its public, revealing multiple challenges and successes in making Native self-representation legible and accessible. Through documentation and analysis of the inaugural exhibits and recent installations, interviews with curators and staff, and investigation into audience reception of these spaces, Legible Sovereignties argues that there can be no single blanket solution for effective Indigenous self-representation. Instead, Legible Sovereignties demonstrates the nuanced ways in which each site must balance its rhetorical goals and its audience's needs, as well as its material constraints and opportunities, in order to reach its visitors and have Indigenous voices heard"--